Leadership of The Head of Madrasah In Improving Student Achievement Through The Management of Non-Academic Activities - An An Andari; Iskandar Zulkarnain; Cipto Handoko; Sri Lestari (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The leadership of the head of the Madrasa is the determining factor for the success of all facilities in Islamic educational institutions. The purpose of this study is to find out how the involvement of the head of the Madrasah in the management of non-academic activities of MA Hidayatul Mubtadiin Jati Agung. The method used is qualitative method. Sources of data are obtained from sources, places, projects or services, and documents. The results show that in managing non-academic activities, MA Hidayatul Mubtadiin Jati Agung implemented several measures, such as: 1) Planning is done by accumulating the number of non-academic activities, providing achievement education and non-academic means of achievement. summarizing the program of non-academic activities in one year 2) The organizational process by gathering all the factors involved in the management of non-academic activities, dividing the work into related matters.